Dynamic Compressive Properties and Failure Mechanism of the Laser Powder Bed Fusion of Submicro-LaB6 Reinforced Ti-Based Composites - Li, Xianghui; Liu, Yang (Micromachines (Basel), 2023)
In this study, lanthanum hexaboride (LaB6) particle-reinforced titanium matrix composites (PRTMCs, TC4/LaB6) were successfully manufactured using the laser powder bed fusion (LPBF) process. Thereafter, the effect of the mass fraction of LaB6 on the microstructure and the dynamic compressive properties was investigated. The results show that the addition of LaB6 leads to significant grain refinement. Moreover, the general trend of grain size reveals a concave bend as the fraction increases from 0.2% to 1.0%. Furthermore, the texture intensity of prior β grains and α grains was found to be weakened in the composites. It was also observed that the TC4/LaB6 have higher quasi-static and dynamic compressive strengths but lower fracture strain when compared with the as-built TC4. The sample with 0.5 wt.% LaB6 was found to have the best strength–toughness synergy among the three groups of composites due to having the smallest grain size. Furthermore, the fracture mode of TC4/LaB6 was found to change from the fracture under the combined action of brittle and ductility to the cleavage fracture. This study was able to provide a theoretical basis for an in-depth understanding of the compressive properties of additive manufacturing of PRTMCs under high-speed loading conditions.